Consistent price endings increase consumers perceptions of cheapness. (July 2021) - Hung, Hui-Hsi; Cheng, Yin-Hui; Chuang, Shih-Chieh; Yu, Annie Pei-I; Lin, Yu-Ting
Abstract: Should marketers make the last digit of a sale price consistent with that of its original price? Across multiple studies, including field studies and studies using student and non-student samples and various product categories, this research shows that price perception and purchase intention are related to consistency between the sale price and original price. The price perception of the deduction is moderated by the consistency between the final digit in the prices. First, consumers perceive sale prices as cheaper and have a higher purchase intention when the rightmost digit in a sale price is the same as in the original price—a phenomenon this study refers to as the "consistent ending price effect." Second, the consistent ending price effect occurs when prices are at least three digits long, but not for two-digit prices. Finally, the study demonstrates the mediating role of processing fluency in the link between consistent ending price and price perception. Highlights: Consumers perceive sale prices as cheaper when the final digit in a sale price is the same as in the original price. Second, the consistent ending price effect occurs when prices are at least three digits long, but not for two-digit prices. The mediating role of processing fluency in the link between consistent ending price and price perception.